Identification of guinea pig remains in the Pucará de Tilcara (Jujuy, Argentina): Evidence in favour of the presence of the Andean breed in the Quebrada de Humahuaca - Lopez Geronazzo, Lautaro Nahuel (2019)
In this article, we identified rodent remains found in the Pucará de Tilcara, an archaeological site from the Argentine Northwest that was occupied by humans from 1,100 ad until the Spanish conquest. The zooarchaeological analyses were carried out using anatomical descriptions and geometric morphometric analyses of the dorsal and ventral views of mandibular remains. The results and the archaeological context discussed showed that all the rodent remains could correspond to the Andean breed of domestic guinea pigs. The combination of the methods used here gave us a strong support to the taxonomical assignment. The presence of domestic guinea pigs in archaeological sites of the northwestern Argentina was never proposed. This approach allowed us to increase knowledge about the distribution of caviines in the region, and their relationship to anthropic processes.